Inhibition of MD2‐dependent inflammation attenuates the progression of non‐alcoholic fatty liver disease. Issue 2 (27th October 2017) - Zhang, Yali; Wu, Beibei; Zhang, Hailing; Ge, Xiangting; Ying, Shilong; Hu, Mengwei; Li, Weixin; Huang, Yi; Wang, Li; Chen, Chao; Shan, Xiaoou; Liang, Guang
Abstract: Non‐alcoholic fatty liver disease (NAFLD) can progress to the more serious non‐alcoholic steatohepatitis (NASH), characterized by inflammatory injury and fibrosis. The pathogenic basis of NAFLD progressing to NASH is currently unknown, but growing evidence suggests MD2 (myeloid differentiation factor 2), an accessory protein of TLR4, is an important signalling component contributing to this disease. We evaluated the effectiveness of the specific MD2 inhibitor, L6H21, in reducing inflammatory liver injury in a relevant high‐fat diet (HFD) mouse model of NASH and in the palmitic acid (PA)‐stimulated human liver cell line (HepG2). For study, genetic knockout (MD2 −/− ) mice were fed a HFD or control diet for 24 weeks, or wild‐type mice placed on a similar diet regimen and treated with L6H21 for the last 8 or 16 weeks. Results indicated that MD2 inhibition with L6H21 was as effective as MD2 knockout in preventing the HFD‐induced hepatic lipid accumulation, pro‐fibrotic changes and expression of pro‐inflammatory molecules. Direct challenge of HepG2 with PA (200 μM) increased MD2‐TLR4 complex formation and expression of pro‐inflammatory and pro‐fibrotic genes and L6H21 pre‐treatment prevented these PA‐induced responses. Interestingly, MD2 knockout or L6H21 increased expression of the anti‐inflammatory molecule, PPARγ, in liver tissue and the liver cell line. Our results provide further evidence for the critical role of MD2 in the development of NASH and conclude that MD2 could be a potential therapeutic target for NAFLD/NASH treatment. Moreover, the small molecule MD2 inhibitor, L6H21, was an effective and selective investigative agent for future mechanistic studies of MD2.